Histopathological, Immunohistochemical, Lectinhistochemical and Molecular Findings in Spontaneous Bovine Abortions by Campylobacter fetus - Morrell, Eleonora Lidia (2011)
Bovine campylobacteriosis (BC) is a venereal disease caused by Campylobacter fetus characterized by temporary infertility with mild endometritis, early embryonic death and occasional abortions. The objectives of this study were to describe and identify C. fetus in spontaneous bovine abortion on the basis of histopathological, immunohistochemical, lectinhistochemical and polymerase chain reaction (PCR) techniques. The most frequent foetal lesion was neutrophilic bronchopneumonia and interstitial pneumonia. Other commonly observed lesions included non‐suppurative interstitial enteritis, hepatitis, pericarditis, myositis, myocarditis, and meningitis. In this study, C. fetus fetus was phenotypically classified in all bovine foetuses from lungs and abomasal fluids. Immunohistochemistry (IHC) staining revealed positive stained Campylobacter organisms with typical morphology. Lectin binding patterns not showed great differences between the infected and the non‐infected groups. The most important changes were a minor peanut agglutinin (PNA) and DBA binding in the alveolar cells of the lungs and DBA globet cells in some of the C. fetus–positive foetuses. Individual variations in each lectin binding pattern complicate the evaluation of the lectins results. All foetuses positive to IHC were positive by PCR. Better efficiency of PCR was obtained from abomasal fluids than from lung tissues. The association of culture and phenotypic techniques with histopathology, IHC and PCR allowed a better characterization and description of BC.